Sistem Identifikasi Faktor Risiko Stunting Pada Balita dengan Decision Tree Berbasis Web (Kasus Desa Margaluyu) - Insany, Gina Purnama; Kamdan, K; Septian, Muhammad Ardhi (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
Stunting is a chronic health issue caused by prolonged nutritional deficiencies, influenced by various risk factors such as economic conditions, sanitation, education, and diet. Margaluyu Village reported a stunting rate of 24.5% in 2023. This study proposes a web-based system that utilizes the Decision Tree algorithm to classify stunting risk among toddlers using attributes like age, weight, height, maternal nutrition status, and environmental sanitation. The model achieved 91.2% accuracy and was implemented using the Laravel framework. The resulting system enables faster and more accurate identification of at-risk toddlers by health workers.